(untitled) (Journal of Dhaka National Medical College & Hospital, 2012)
Objectives: To determine the oral hygiene practices, periodontal status and bad mouth breath (BMB) among the children age between 5 to 15 years. Study participants and methods: This was a cross sectional descriptive study conducted at at four-selected primary school at Fultola and Juri Upazilla of Moulovi Bazar District. Total 250 children aged 515 years, were interviewed on oral hygiene practices and BMB using structured questionnaire and a checklist. Oral hygiene and periodontal status were assessed by using disposable dental explorer and a dental mirror. Results: Oral hygiene practice were; where (66.8%) non tooth brush and tooth brush users were (33.2%). The prevalence of dental caries plaque, gingival bleeding and BMB on probing was (69.6%), (91.6%), (66.8 %) and (64%) respectively. Conclusion: Bad mouth breath is a cause of concern among children associated significant factors were gum bleeding. Research involving clinical diagnosis of bad mouth breath and intervention through oral health promotion and periodontal therapy are recommended. Clinical relevance: This study provides baseline information on oral health status and bad mouth breath which necessitates in the future need for objective assessment, diagnosis and management of bad mouth breath for enhanced social and professional interaction without embarrassments. DOI: http://dx.doi.org/10.3329/jdnmch.v18i1.12240 J. Dhaka National Med. Coll. Hos. 2012; 18 (01): 43-48